P482 Safety and efficacy of ustekinumab for Crohn's disease in the elderly population. (27th May 2021) - Fiske, J; Liu, E; Limdi, J; Conley, T E; Townsend, T; Davies, M; Brockwell, R; Baig, D; Abdelbadiee, S; Uney, A; Liaros, A; Gaba, W; et al.
Abstract: Background: The rising incidence of inflammatory bowel disease (IBD) worldwide and an ageing population has led to a marked increase in elderly IBD patients. Anti-tumour necrosis factor (TNF) agents are associated with an increased risk of serious infections and treatment discontinuation among elderly IBD patients but little is known about non anti-TNF biologics in this cohort. We aimed to examine safety and efficacy of ustekinumab in elderly Crohn's disease (CD) patients. Methods: Patients ≥60 years old commencing ustekinumab for CD were included in this retrospective multi-centre cohort study. We gathered data on adverse events, Harvey Bradshaw Index (HBI) and concomitant steroid therapy. The primary outcome was serious infections, defined as requiring hospitalisation. Efficacy was assessed by serial HBI measurement and treatment persistence. Results: 70 patients were included, with a median age of 68 years (range 60–87), a male:female ratio of 9:5 and a median Charlson co-morbidity index of 4 (range 2–9). 44 (62.9%) had prior anti-TNF exposure and 15 (21.4%) previous vedolizumab. Median treatment duration was 12 months (range 2–48), with a total of 84 patient years. 31 patients (41.3%) had steroids at initiation, and 33 (47.1%) required a course of steroids at a later date. Seven patients (10%) had a combined 9 serious infections, of which 1 was life threatening requiring organ support. Incidence of serious infections was 0.107 per patient year. A further 18 patients had a combined 22 non-severe infections (Table 1). The overall infection rate was 0.417 per patient year. Charlson co-morbidity index was numerically higher among those who developed severe infections (median 5, range 3–7 vs. median 4, range 2–9, P=NS). 3 patients developed a malignancy; non-Hodgkin's lymphoma, melanoma and prostate cancer. Mean HBI improved from 8.13 at baseline to 4.64 at 6 months and 4.10 at last follow up (both P<0.0001). Treatment persistence rate was 61.4% (N=43) and 36 (51.4%) were steroid-free. Reasons for discontinuation were primary non-response (42%), adverse event (32%), secondary loss of response (10%), malignancy (10%) and lack of funding (5%). Conclusion: Ustekinumab was safe and effective in a cohort of elderly CD patients. Infections were mostly mild, not resulting in therapy discontinuation. The risk of serious infection was low at 0.107 per patient year of treatment.